Motor vehicles pollutions / Maizatul Akma @ Maimun Mohamad - Mohamad, Maizatul Akma @ Maimun (2004)
This project carried out with the objective to give a sense of responsibility to the environment. Then we will study about motor vehicles pollutions, the pollutants and overcoming for that. The total of vehicles in Malaysia was 10.6 million and the total of vehicles Kuala Lumpur was 2.2 million. The causes which come from motor vehicles are noise pollutions and photochemical smog. The type of air pollutants are carbon monoxide, sulfur dioxide, nitrogen oxides, hydrocarbon and others. Government had always checked the mechanical mandatory for motor vehicles and make sure the vehicles follow the rules. Government also can make a sport check randomly for all of motor vehicles and make sure the vehicles follow up the rules of smog released. The public has become too aware about these problems. So that, the problem can be solve perfectly.